2010
DOI: 10.1517/14712591003774063
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immunotherapy of multiple myeloma: perspectives and perplexities

Abstract: mAbs directed against MM-associated adhesion markers should be taken into account in clinical practice, since they could possibly represent the best available combination of tumor cytotoxicity, environmental signal deprivation and immune system redirection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…25,26 Earlier studies have shown that PSGL-1 is highly expressed in MM, 22,27 is a novel therapeutic target for mAb-mediated MM immunotherapy, plays a role in humoral immunotherapy of MM, and combined treatment with PSGL-1 mAb and chemotherapy improves tumor cytotoxicity. 23,28 In the present study, we targeted PSGL-1 by inhibiting its interaction with selectins in the microenvironment as a therapeutic prospect but with a focus on adhesion dynamics that involve PSGL-1 on MM cells and its interaction with selectins in the BM microenvironment. We show that PSGL-1 regulates the adhesion and homing of MM cells to cells in the BM microenvironment, including ECs and BM stromal cells (BMSCs).…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Earlier studies have shown that PSGL-1 is highly expressed in MM, 22,27 is a novel therapeutic target for mAb-mediated MM immunotherapy, plays a role in humoral immunotherapy of MM, and combined treatment with PSGL-1 mAb and chemotherapy improves tumor cytotoxicity. 23,28 In the present study, we targeted PSGL-1 by inhibiting its interaction with selectins in the microenvironment as a therapeutic prospect but with a focus on adhesion dynamics that involve PSGL-1 on MM cells and its interaction with selectins in the BM microenvironment. We show that PSGL-1 regulates the adhesion and homing of MM cells to cells in the BM microenvironment, including ECs and BM stromal cells (BMSCs).…”
Section: Introductionmentioning
confidence: 99%
“…Use of mAbs in combination with conventional chemotherapy has become the standard of care for various diseases [52]. For a mAb-based therapy to be effective against MM, the target antigen should be expressed in a high percentage of neoplastic plasma cells, components of the bone marrow microenvironment such as marrow stromal cells, or cells of the immune system that mediate immune response [53,54]. The chimeric mAb against CD20, namely rituximab, is a well-established therapy for B-cell lymphomas and has been investigated for MM.…”
Section: Therapeutic Monoclonal Antibodies Against MMmentioning
confidence: 99%
“…A wide range of antigens may be targeted in MM therapy and they include cell surface receptors, signaling molecules involved in cell survival, antiapoptotic pathways and cell-to-cell communication, and the interactions between MM cells and bone marrow stromal cells. 13 Several diverse mAbs are currently being evaluated in preclinical and clinical studies. Mechanisms of action of these mAbs include antibody-dependent cellular cytotoxicity (ADCC), complement-dependent cytotoxicity (CDC), interference with receptor-ligand interactions, and mAb conjugation to radioisotopes or toxins.…”
Section: Immunotherapy In MMmentioning
confidence: 99%